Identification of the main diseases of cotton and application of the combined protection method (Eurasian Research Bulletin, 2024)
Cotton is a major crop in parts of the African Tropics, Australia, China, Egypt, India, Mexico, Pakistan, Soviet Union, the Sudan, United States, and warmer regions of Central and South America. Diseases have always been a problem wherever cotton is grown1. Under the conditions of Uzbekistan, the productivity of cotton is significantly decreasing due to several diseases. Below are the diseases that have a negative effect on cotton and their main symptoms, as well as the substances used to fight against them, and their consumption standards